False because the answer would be -10
Answer:
1. single sample design
2. matched pairs
3. two independent samples.
Step-by-step explanation:
the response variable is known as the dependent variable, it is the variable that the researcher is interested i finding. the response variable is the x variable that responds to changes in the independent variable.
1.
In this question the researcher has only one sample that is the specimen. that is the reference specimen that she obtained. Therefore it is a single sample design.
the response variable here is the measurement of concentration.
2. In this question we have two pairs, men and women. The researcher is interested in comparing attitudes as she interviews them. so response variable is attitude or behavior
3. this is a 2 independent sample design. The researcher is using two different methods to test and their average is being compared.
Standard Form : f (x) = a(x - h)2 + k
Where in this equation (H,K) is the vortex of the parabola
<u>and there are four other ways to solving these quadratic</u>
1. Factoring
2. Completing the square
3. Your quadratic formula ( f (x) = a(x - h)2 + k )
4. Graphing
Answer:
y = 50x+25
f(x) = 50x+25
Step-by-step explanation:
Using the slope intercept form of the equation, y = mx+b
where x is the amount per day and b is the flat fee
2 days
125 = 2x+b
5 days
275 = 5x+b
Subtract
275 = 4x+b
125 = 2x+b
---------------------
150 = 3x
Divide by 3
150/3 = 3x/3
50 =x
The cost per day is 50 dollars
y = 50x +b
Using the data for 2 days
125 = 50*2 +b
125 = 100 +b
125-100 = b
b = 25
The equation is y = 50x+25
f(x) = 50x+25
To graph, The x axis is number of days and the y axis is total cost
The number of days starts with 0, which is the y intercept
Let x = 0, y =25
Using the slope, we go 50 up and 1 to the right ( 50 dollars per day)
The next point plotted ins ( 1,50)
Draw a straight line
In order to solve this, we need to select the function that meets our constraints. Since x^2 - 5 occurs when x is less than 3, and the x-value we are given is -4, we use the first function.
f(-4) = (-4)^2 - 5
f(-4) = 16 - 5
f(-4) = 11